Model Index Card Match: Active Students in Class on Prayer Material - Febi Angraeni; Hikmah Nur Fajriyah; Imam Tabroni; Sania Rahmania (International Journal of Integrative Sciences, 2023)
The learning model is a design or flow that is planned by the teacher when carrying out learning activities in order to achieve learning objectives. The existence of this learning model as a teacher’s guide when teaching in class. The Index Card Match learning model is a learning model that can make students active while learning, its use is by using cards that contain questions and answers and are given to students randomly. The purpose of this study was to determine the effect of student learning outcomes when using the Index Card Match model on prayer material in class IV A SD Negeri Sempur. In this study, the researcher used a quantitative experimental research method, in which the researcher tried to apply a new learning model that had never been applied before at SD Negeri Sempur, namely the Index Card Match model